2016
DOI: 10.5152/etd.2016.0052
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Risk Factors for Arteriovenous Fistula Failure in Patients Undergoing Hemodialysis

Abstract: Objective: The aim of the present study is to evaluate the relationship between demographic characteristics, hematological and biochemical parameters, and elements of the coagulation system that may predispose a person to thrombosis or to anatomical and functional parameters in Doppler ultrasonography scanning and the maturation and adequacy of arteriovenous fistulas. Materials and Methods:Overall, 36 patients who underwent a native arteriovenous fistula operation were included. Biochemical parameters, hematol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Screening for anticoagulant factors which can predispose a person to hypercoagulability is highly recommended in patients undergoing hemodialysis and are potential candidate for renal transplant as a precautionary measure to decrease the risk of subsequent graft rejection. 17 From literature review we see that the PC & PS deficiencies are more common as well as stronger risk factors for thromboembolism as compared to antithrombin and factor V mutation and may be helpful in forecasting the risk of thromboembolism in Asians. 18,19 In our study we found 6.66% patients had PC deficiency and 4.0% had PS deficiency.…”
Section: Discussion Discussionmentioning
confidence: 99%
“…Screening for anticoagulant factors which can predispose a person to hypercoagulability is highly recommended in patients undergoing hemodialysis and are potential candidate for renal transplant as a precautionary measure to decrease the risk of subsequent graft rejection. 17 From literature review we see that the PC & PS deficiencies are more common as well as stronger risk factors for thromboembolism as compared to antithrombin and factor V mutation and may be helpful in forecasting the risk of thromboembolism in Asians. 18,19 In our study we found 6.66% patients had PC deficiency and 4.0% had PS deficiency.…”
Section: Discussion Discussionmentioning
confidence: 99%
“…In a 2014 study, of 338 autologous AVFs, 326 patients had obvious AVFs for dialysis (96.4% surgical success rate, or 3.6% AVF failure rate) (13). Sari et al detected AVF failure in 81 patients out of 831 studied cases (rate = 10%) (14), and Monroy-Cuadros et al reported 15.3% for incidence rates of primary AVF filure and never using AVF after operation (15).…”
Section: Discussionmentioning
confidence: 99%
“…From another perspective, performing a meta-analysis on published researches concludes many inscrutable points in different studying conditions; for example, there are conflicts on risk of BP toward AVF failure. While a study in 2016 on 36 HD patients did not find any relationship between BP and thrombosis formation (p>0.05) (14), in 2 more detailed reviews on 87 HD patients, a significant relationship was found between the systolic blood pressure (SBP) and the delay of AVF maturation (30). Moreover, under publishing research in Nature journal, which was done on 480 HD patients, indicated that the patients with a positive history of hypertension have more matured AVF (31).…”
Section: Discussionmentioning
confidence: 99%
“…Kaygin et al found no relationship between total protein and AVF maturation outcomes [24]. Also, Sari et al found no correlation between total protein level and AVF thrombosis [25].…”
Section: Serum Ironmentioning
confidence: 99%